Prevention and Treatment of Periodontitis - Ogata, Yorimasa; Imai, Kenichi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a compilation of articles by experts on the prevention and treatment of periodontal disease, many of which are full of data-based evidence from basic research perspectives or patient data.